Ambulatory blood pressure monitoring in the 21st century - O'Brien, Eoin (J Clin Hypertens (Greenwich), 2018)
In clinical practice, ambulatory blood pressure monitoring (ABPM) tends to be used solely for diagnosing hypertension, especially to identify white‐coat and masked hypertension. However, ABPM can provide additional information to guide the management and drug treatment of hypertension. In this brief review, the general principles governing the use of ABPM in clinical practice, such as the devices and software, recording requirements, the thresholds for the day, night and 24‐hour periods and how often to repeat ABPM are summarized. The use of ABPM for diagnosing, determining the efficacy of treatment, and assessing the long‐term control of hypertension are discussed.